2012
DOI: 10.2478/10004-1254-63-2012-2213
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Metal Nanoparticles: Focus on In Vivo Studies

Abstract: With increasing production and application of a variety of nanomaterials (NMs), research on their cytotoxic and genotoxic potential grows, as the exposure to these nano-sized materials may potentially result in adverse health effects. In large part, indications for potential DNA damaging effects of nanoparticles (NPs) originate from inconsistent in vitro studies. To clarify these effects, the implementation of in vivo studies has been emphasised. This paper summarises study results of genotoxic effects of NPs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 39 publications
3
35
1
Order By: Relevance
“…Another way by which NPs can cause genotoxic damage is through their surface charge and time of exposure. Our results are consistent with that of Klien and Godnić-Cvar (2012), which showed that 1-2-day exposure is sufficient to cause DNA strand breaks. However, differences in exposure methods must be considered.…”
Section: Discussionsupporting
confidence: 92%
“…Another way by which NPs can cause genotoxic damage is through their surface charge and time of exposure. Our results are consistent with that of Klien and Godnić-Cvar (2012), which showed that 1-2-day exposure is sufficient to cause DNA strand breaks. However, differences in exposure methods must be considered.…”
Section: Discussionsupporting
confidence: 92%
“…Klien and Godnić-Cvar [20] believed that the Co NPs have rarely been considered to induce DNA damage in vivo. Hereby, we have recorded a significant induction of MN in MnPCEs/1000 PCEs that might be due to chromosomal break/damage leaving a part of chromosome or the whole chromosome in the mature cell [21], reproductive toxicity appeared in the form of decrease in sperm motility, concentration, and increased sperms abnormalities and DNA damage in comet assay in comparison to negative control group.…”
Section: Discussionmentioning
confidence: 99%
“…Nano-bio interference can result in detrimental biological effects like generation of reactive oxidative species (ROS), cytotoxicity, genotoxicity and inflammatory responses [8,9]. In recent years, the number of studies about the toxic risks of NPs is increasing [10].…”
Section: Discussionmentioning
confidence: 99%